Measuring the thickness and Young's modulus of the ice pack with DAS, a test case on a frozen mountain lake. Issue 2 (23rd December 2022) - Nziengui-Bâ, Destin; Coutant, Olivier; Moreau, Ludovic; Boué, Pierre
SUMMARY: We explored the potential of fibre optics coupled with distributed acoustic sensing (DAS) to measure the thickness and Young's modulus of an ice layer, using the properties of guided seismic waves. During two winter seasons (2020 and 2021), an optical fibre was deployed over one of the frozen Roberts Mountain lakes (at 2400 m a.s.l) near Grenoble (France) and we measured both the continuous ambient seismic noise as well as signals generated by active sources (hammer), with a DAS interrogator. Following a Bayesian scheme, we inverted the dispersion curves of longitudinal and flexural guided waves retrieved from the analysis of active shot gathers and obtained Young's modulus E = 3.4 ± 0.1 GPa and ice thickness h = 47 ± 1 cm from the second-year data. The ice thickness was consistent with field measurements. Field observations of porous and/or fracture ice may explain the relatively low effective Young's modulus (relative to pure ice), which may also be affected by a snow layer not included in the model. The drastic improvements in the inversion results between the two years are related to better coupling conditions (drone deployment before early freezing), more appropriate acquisition parameters (2 m gauge length), and the upper snow layers (less thick and less heterogeneous in the second year). Moreover, we were able to use the non-dispersive low-frequency noise associated with gravity waves to estimate the lake depth H = 5 m which is compatible with independent observations. The use of DAS to record guided seismic waves could then appear as a relevant tool for monitoring environments like floating ice shelves and sea ice.